Enhancing a Dichotomous Test Item to Enhance the Assessment of Undergraduates’ Reading Skills - Sarmatha, S. (Faculty of Graduate Studies, University of Sri Jayewardenepura., 2019)
In the pedagogic scenario, teaching, learning and evaluation are interdependent, and the teaching process is clearly established by evaluating system because if a test is not properly designed and planned that may result in harmful impacts on teaching and learning. A test means, in terms of language teaching, focusing on the target language abilities assessed by a measurement instrument designed by an examiner. Ranking, scores or grades of the test show several attributes of testees, strengths and weakness of a test item and washback on language teaching. Thus, the researcher intended to explore the current test item in order to enhance the assessment of language learners’ reading skills in the backdrop of the tertiary level education. The aim of this study is to enhance a dichotomous test item to improve undergraduates’ reading skills, and the basic purpose of this study is to analyse results of the test for making decisions in regards to developing an existing test item in reading skills. This study is based on a quantitative methodology to discover Item Facility (IF), Item Discrimination (ID) and Distractor Efficiency (DE) and descriptive analysis to synthesise and discuss the results of the study to enhance the test item in future assessment. Data were collected by a designed test item to test the reading skills to the first-year ESL learners in a faculty of Business Studies, and the scripts were marked to analyse the results and to develop the existing test item. The results of this study show that the test item: multiple choice questions and true/ false questions need to be developed in order to construct a plausible test item and this study proposed an alternative test item as well.
Keywords: Dichotomous; Reading skills; Evaluation; Test item; Upgrading